PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL SHERATON BANDUNG - Wahyudi Ilham; Br Pakpahan, Tiara Joy Disry; Pratama, Tito; Sukmamedian, Haufi (Puslitabmas Batam Tourism Polytecnic, 2024)
Leadership has a positive and significant partial effect on the performance of Food & Beverage Service employees at Sheraton Bandung Hotel & Towers. This suggests that if department managers effectively coordinate their teams, employee performance will improve. The work environment also positively and significantly impacts the individual performance of Food & Beverage Service employees at Sheraton Bandung Hotel & Towers, indicating that a supportive and conducive work environment enhances performance. Both leadership and the work environment together have a positive and significant impact on the performance of Food & Beverage Service employees at Sheraton Bandung Hotel & Towers. The research design utilized by the researcher is a quantitative approach. The author employed an explanatory research type, specifically associative research, which aims to test theories or hypotheses to either confirm or refute existing theories or hypotheses based on prior research findings. The study focuses on the variables of leadership, work environment, and employee performance in the Food & Beverage Service at Sheraton Bandung Hotel & Towers. The objectives of this research are: To identify the impact of leadership on the quality of employee performance at Feast Restaurant in Sheraton Bandung Hotel and Towers. To examine the effect of the work environment on the quality of employee performance at Feast Restaurant in Sheraton Bandung Hotel and Towers and To determine whether leadership or the work environment has the most significant influence on the quality of employee performance at Feast Restaurant in Sheraton Bandung Hotel and Towers.